Anxiety Levels of Medical Students in Online Learning During COVID-19 Pandemic - Amadeus, Joachim Kenneth; Veronica, Fifi; Oktavia, Nandina; Wahyudi, Kurnia; Lydiana, Lynna (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: The COVID-19 pandemic has affected the education sector and caused major changes. This situation provides challenges for students, resulting in increased anxiety, especially for medical students who tend to have higher level of anxiety. This study aimed to determine the proportion of anxiety levels among undergraduate medical students in online learning during the COVID pandemic.Methods: This cross-sectional descriptive study was conducted in September–November 2022, involving 156 undergraduate medical students at Universitas Padjadjaran, Indonesia batch 2019–2021 who had no history of somatic or psychiatric disease. The stratified simple random sampling method was used. Anxiety levels was assessed using the Hamilton Anxiety Rating Scale (HAM-A) questionnaire. Data was analyzed using Pearson’s Correlation.Results: Participants were dominated by females (71.1%), average age 19.9 years with a grade point average (GPA) of 3.51-4.00 (88.5%). The anxiety level of most participants was mild (67.9%) and 19.2% were at the severe level. Interestingly, severe levels of anxiety seemed to occur more commonly in females, group batch 2020, GPA 2.51-3.00, living alone and in a place other than in the family home or rented house. Furthermore, respiratory manifestations tended to be the mildest, whereas intellectual manifestations were more often severely impacted.Conclusions: The anxiety level of undergraduate medical students in Universitas Padjadjaran is mostly mild. Female more often experience anxiety at a more severe level. Further research is needed to identify and analyze more comprehensively other possible anxiety factors in medical students.